Biliary atresia screening in Shenzhen: implementation and achievements. Issue 8 (9th June 2020) - Zheng, Jiachen; Ye, Yongqin; Wang, Bin; Zhang, Lihui
Abstract : Objective: To elaborate on the implementation and achievements of a biliary atresia (BA) screening programme in Shenzhen. Methods: In 2015, we partnered with the government in Shenzhen and attached the stool colour card (SCC) to the health handbook for mothers and children. These handbooks have been distributed through official channels to every pregnant woman in Shenzhen since 1 January 2015. A total of 118 patients diagnosed with BA at Shenzhen Children's Hospital were enrolled and divided into two cohorts based on their date of diagnosis: cohort A before and cohort B after introduction of screening. The cohorts were compared to evaluate differences in age at diagnosis, jaundice-free rate, 2-year native liver survival rate and so on. Results: After the implementation of the screening programme, the age at diagnosis decreased from 81±12 to 56±15 days old (p<0.05), the incidence of postoperative complications decreased from 58.8% to 52.6% (p<0.05), the jaundice-free rate increased from 47.1% to 54.4% (p<0.05), and the 2-year native liver survival rate increased from 44.4% to 52.6% (p<0.05). The percentage of patients who underwent surgery increased from 68.0% to 83.8% (p<0.05). Conclusion: In Shenzhen, our screening programme led to earlier diagnoses and better prognoses. The latter resulted in an increased willingness to undergo the Kasai procedure. Through a hospital and government collaboration, this programme exerted a considerable influence, and guardians observed benefits with only a small cost of implementation. Our results may eventually help promote the widespread use of the SCC across the whole country.